Effect of tellurium on the microstructure and mechanical properties of Fe-14Cr oxide-dispersion-strengthened steels produced by additive manufacturing. (30th December 2021) - Arkhurst, Barton Mensah; Bae, Jee Hwan; Na, Min Young; Chang, Hye Jung; Kim, Hyun Gil; Kim, Il Hyun; Ryu, Ho Jin; Kim, Jeoung Han
Abstract: Conventionally, Te has primarily been used to improve the machinability of steel and its alloys. In this work, Te was used to refine the grains of an oxide-dispersion-strengthened (ODS) steel produced by additive manufacturing (AM) with fixed processing parameters. Addition of Te to the raw powder produced an ODS steel with a fine-grained microstructure, in contrast to the ODS steel manufactured without Te. Moreover, the addition of Te resulted in superior yield strength and ultimate tensile strength, which was attributed to the combined effects of grain refinement and the finer nanoparticles (NPs) composed of Te-rich composite NPs and Cr-rich NPs. For the first time, the AM technique was used to obtain grain and nanoparticle sizes of 3.4 µm and 6 nm, respectively, from the Te-added ODS steel Graphical abstract: Image, graphical abstract